Социальные аспекты выбора профессии в молодежной среде - Шовковий, Є. І. (ХНУРЕ, 2021)
The article deals with the problems of vocational training of young people for working professions. Article also shows that in the actual public consciousness a fairly stable idea of blue-collar professions has been formed as bankrupt and outdated. Especially when it comes to blue-collar occupations in industry. When young people choose their future profession, it is not only external, but also internal motivation that is of great importance, that is, the attitude of a young person to his working labor, meaningful, creative motives, ideas about the intrinsic value of working labor.
Keywords: философия; выбор профессии